Ineffective Thermoregulation (NANDA) In: Nursing diagnoses: definitions and classification, 1997-1998. (Ineffective Thermoregulation (NANDA) In: Nursing Diagnoses: Definitions & Classification, 1997-1998, 1996)
SCOPE NOTE: The state in which an individual's temperature fluctuates between hypothermia and hyperthermia. Use only as a specific North American Nursing Diagnosis Association nursing diagnosis. Copyright (c) 1996, North American Nursing Diagnosis Association. CINAHL EDITORIAL SEARCH SUGGESTION: The term INEFFECTIVE THERMOREGULATION (NANDA) is used for indexing when articles specifically concern the term or research about the term. For citations that concern the general topic or topics related to the term, consider searching the subject heading: BODY TEMPERATURE REGULATION.